Chlamydial bacteriophage: No Role in Acute Coronary Events?. Issue 5 (2005) - Patrick, David M; Karunakaran, Karuna; Levy, Adrian R; Gin, Kenneth; Remple, Valencia; Chong, Mei; Abbey, Heather; Tarry, Laura; Shen, Caixia; Brunham, Robert C
Abstract : BACKGROUND: A relationship between Chlamydia pneumonia e infection and acute coronary syndromes has not been consistently found in published studies. It has been hypothesized that a bacteriophage-infected subset of C pneumoniae may be uniquely equipped to promote atherosclerosis and acute coronary syndromes through the expression of phage genes. METHODS: The authors performed a pilot case-control study of acute coronary events. Case and control subjects were characterized demographically and according to recognized coronary risk factors. These subjects also provided serum for the detection of antibody to the elementary bodies of C pneumoniae and antibody to the Vp1 protein coded by the phage. Bivariate and multivariate comparisons were performed using statistics appropriate for paired analyses. RESULTS: Antibodies to C pneumoniae, Vp1 protein or both were not associated with acute coronary events by bivariate or multivariate analysis. As expected, case subjects were significantly more likely to have hypertension, hypercholesterolemia or diabetes mellitus. CONCLUSION: The present study adds to a growing body of literature that does not support the hypothesized relationship between C pneumoniae (or a phage-infected subset of C pneumoniae ) and acute coronary syndromes.